1997
DOI: 10.1093/oxfordjournals.eurheartj.a015236
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of cardiac physiology by tissue Doppler echocardiography: A comparison with invasive haemodynamics

Abstract: Tissue Doppler echocardiography has the potential to accurately measure the different phases of the cardiac cycle which until now could only be determined invasively. It may provide a sensitive method for the assessment of changes in both cardiac contraction and relaxation in different clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
5

Year Published

1998
1998
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 23 publications
1
42
0
5
Order By: Relevance
“…The increase in Sw1 along the long axis contributes to spherical changes in the LV cavity during isovolumic contraction phase [23], and therefore a decrease in this peak velocity can be useful in the early diagnosis of impaired contractility in elderly individuals with normal LV pump function [24,25]. With respect to the TDI findings during early systole, Zamorano et al [26] simultaneously recorded M-mode color TDI and LV-aortic-left atrial pressures, and reported that there was a good correlation between the time interval assessed hemodynamically and that based on the velocity interface obtained with M-mode color TDI during the isovolumic contraction phase. Another study reported that there is a positive correlation between the preejectional peak velocity and LV ejection fraction in normal individuals [27].…”
Section: Systolic Functionmentioning
confidence: 99%
“…The increase in Sw1 along the long axis contributes to spherical changes in the LV cavity during isovolumic contraction phase [23], and therefore a decrease in this peak velocity can be useful in the early diagnosis of impaired contractility in elderly individuals with normal LV pump function [24,25]. With respect to the TDI findings during early systole, Zamorano et al [26] simultaneously recorded M-mode color TDI and LV-aortic-left atrial pressures, and reported that there was a good correlation between the time interval assessed hemodynamically and that based on the velocity interface obtained with M-mode color TDI during the isovolumic contraction phase. Another study reported that there is a positive correlation between the preejectional peak velocity and LV ejection fraction in normal individuals [27].…”
Section: Systolic Functionmentioning
confidence: 99%
“…These phases were defined using the combined information derived from M-mode images taken at the tips of mitral valve leaflets with visible valve openings and the simultaneously recorded ECG and phonocardiogram. 17,20,28 To obtain M-mode DMI images, the echocardiographic examination was extended by 2 to 3 minutes. Another 5 to 10 minutes were used for off-line analysis of images.…”
Section: Doppler Myocardial Imagingmentioning
confidence: 99%
“…The potential of identifying subendocardial impairment due to nontransmural ischaemia that is not detectable by twodimensional echocardiography could add important information during provocative tests. It has also been noted that several changes in myocardial layer velocities derived from Doppler tissue imaging could represent a mean for the non-invasive assessment of vessel patency early after the onset of acute myocardial infarction [46,47] . If successful, the non-invasive prediction of vessel patency after thrombolytic therapy, based on serial assessment of regional systolic and diastolic myocardial velocities, could impact on the need for early invasive testing and rescue angioplasty in patients treated with thrombolytics during acute myocardial infarction.…”
Section: Future Clinical Applications In Myocardial Ischaemiamentioning
confidence: 99%